2021
DOI: 10.5194/essd-13-4779-2021
|View full text |Cite
|
Sign up to set email alerts
|

The Bellinge data set: open data and models for community-wide urban drainage systems research

Abstract: Abstract. This paper describes a comprehensive and unique open-access data set for research within hydrological and hydraulic modelling of urban drainage systems. The data come from a mainly combined urban drainage system covering a 1.7 km2 area in the town of Bellinge, a suburb of the city of Odense, Denmark. The data set consists of up to 10 years of observations (2010–2020) from 13 level meters, 1 flow meter, 1 position sensor and 4 power sensors in the system, along with rainfall data from three rain gauge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 64 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…For instance, at the calibration stage for rainfall event 4 as shown in Figure 13c, the deviations of the peak water depth at site 2 estimated by ES‐MDA and ES‐ILU (0.05 and 0.07 m respectively) are much lower than those obtained by Pedersen et al. (2021) (0.55 m). For the validation of the model predictions for rainfall event 3 at site 2 as shown in Figure 12c, the peak times estimated by ES‐MDA and ES‐ILU are 4 and 3 min earlier than the observations, respectively, while it is 15 min earlier for the estimation by Pedersen et al.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…For instance, at the calibration stage for rainfall event 4 as shown in Figure 13c, the deviations of the peak water depth at site 2 estimated by ES‐MDA and ES‐ILU (0.05 and 0.07 m respectively) are much lower than those obtained by Pedersen et al. (2021) (0.55 m). For the validation of the model predictions for rainfall event 3 at site 2 as shown in Figure 12c, the peak times estimated by ES‐MDA and ES‐ILU are 4 and 3 min earlier than the observations, respectively, while it is 15 min earlier for the estimation by Pedersen et al.…”
Section: Resultsmentioning
confidence: 67%
“…Specifically, for the real‐world case, both the ES‐MDA and ES‐ILU methods provide better calibration results than the best‐known solution manually obtained by Pedersen et al. (2021). It is found that a good overall fit to the observed data does not necessarily guarantee the good accuracy of estimations for all model states.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations